Valine induces inflammation and enhanced adipogenesis in lean mice by multi-omics analysis - Zheng, Hui-Yi; Wang, Li; Zhang, Rong; Ding, Ran; Yang, Cai-Xia; Du, Zhi-Qiang (Frontiers in Nutrition, 2024)
Introduction: The branched-chain amino acids (BCAAs) are essential to mammalian growth and development, but aberrantly elevated in obesity and diabetes. Each BCAAs has an independent and specific physio-biochemical effect to the host. However, the exact molecular mechanism of valine’s detrimental effect in metabolic health remains largely unknown. Methods and Results: This study showed that for lean mice treated by valine, the hepatic lipid metabolism and adipogenesis were enhanced, and the villus height and crypt depth of ileum were significantly increased. Transcriptome profiling on white and brown adipose tissues revealed that valine disturbed multiple signaling pathways (e.g. inflammation, fatty acid metabolism). Integrative cecal metagenome and metabolome analyses found that abundances of Bacteroidetes decreased, but Proteobacteria and Helicobacter increased, respectively; and 87 differential metabolites were enriched in several molecular pathways (e.g. inflammation, lipid and bile acid metabolism). Furthermore, abundances of two metabolites (stercobilin and 3-IAA), proteins (AMPK/pAMPK and SCD1) and (inflammation and adipogenesis-related) genes were validated. Discussion: Valine treatment affects the intestinal microbiota and metabolite compositions, induces gut inflammation and aggravates hepatic lipid deposition and adipogenesis. Our findings provide novel insights into and resources for further exploring the molecular mechanism and biological function of valine on lipid metabolism.